TIMING STRATEGIES IN COOPERATION AMONG CULTURAL AND ART INSTITUTIONS - Wójcik, Dagmara; Juszczyk, Patrycja (Organizacja i Kierowanie, 2023)
In the field of strategic management, strategies have been so far considered mainly in the long-term horizon, as a deliberately planned process with previously defined goals. Thus, the aspect of spontaneous, sudden, impulsive or even intuition-based actions, encouraging the use of emerging opportunities in the organization’s environment, also in relation to cooperation with other entities, was omitted. At the same time, it has been shown that inter-organizational cooperation is a relationship that may be short-term, temporary, incremental, emerging spontaneously, which is particularly visible among cultural and art institutions due to the specific nature of their activities. The aim of the article is to present the importance of time and the appropriate moment to take action and exemplification of the use of chances in the cooperation of cultural and art institutions based on timing strategies. The study is based on a qualitative, interpretive approach using 50 semi-structured interviews conducted in the performing arts sector among public and private theaters. The study not only identified but also illustrated the use of four timing strategies in inter-organizational cooperation of cultural and art institutions that relate to the usage of chances in the environment, i.e.: chance-grasping strategy, chance-entraining strategy, chance-riding strategy and chance-creating strategy. The article shows their use in performing arts using specific examples. Research results prove that cultural and art institutions cooperate on a temporary, ad hoc basis, taking advantage of favorable moments and opportunities emerging in the environment, hence they use different timing strategies, adapted to the current situation and the prevailing needs of the organization.